ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI LUAS AREAL DAN PRODUKSI KARET DI KOTA PAGAR ALAM - Effendie, Nurhayati Oktavia; Iswarini, Harniatun; Iskandar, Sutarmo (Universitas Muhammadiyah Palembang, 2013)
ABSTRACT This study aimed to find out how domestic coffee prices factors, the of domestic rubber prices, and interest rates affecting the area of rubber Pagar Alam, to find out how rainfall, labor wage rate factor, and the total area of rubber affects the production of rubber in Pagar Alam . This research has been carried out by taking a secondary data about the rubber in Pagar Alam. Time data collection was conducted in May - July 2012. The research method used in this research secondary data method, data collection methods used are secondary data (time series). Processing and data analysis methods affect the total area and production of Pagar Alam rubber, Multiple linear regression analysis is used. The results showed that the variables of domestic rubber prices, the domestic coffee prices, interest rates together - the same significant effect on the total area of the City Pagar Alam rubber. Partially variable domestic coffee price and domestic rubber price has a significant influence on the total area of Pagar Alam rubber. As for the domestic rubber prices variables are non-significant effect on the total area of Pagar Alam rubber. As for the variable rainfall, labor wage rates, the area under rubber in common - each had a significant influence on rubber production variables Pagar Alam. Partial variable wage labor rates and area under rubber hase a significant influence the production of Pagar Alam rubber. As for the rainfall variable are non significant effect on the production of Pagar Alam rubber.